Implementation of the Numbered Heads Together Learning Model to Improve Students’ Learning Outcomes - Putri Suri Anjani; Celine Aloyshima Haris (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to determine how the implementation of the Numbered Heads Together (NHT) learning model contributes to the improvement of students’ learning outcomes. The method used was a pre-experimental approach with a One-Group Pretest–Posttest design, involving only one class as the experimental group, without a control class. Data were collected through a pretest and a posttest, and then analyzed using the Normality test and the Hypothesis test (Paired Sample T-Test) with the SPSS Version 25 program. The research results showed that the average posttest score was 80.34, with the Paired Sample T-Test yielding a t-value of 9.396 and a significance level of 0.000 (p < 0.05), exceeding the established Minimum Mastery Criteria. These findings show that implementing the Numbered Heads Together learning model significantly improved students’ learning outcomes. Therefore, Numbered Heads Together can be used as an effective learning model to enhance the effectiveness of the learning process